Neurological and Cognitive Performance After Childhood Encephalitis - Pöyhönen, Heidi; Setänen, Sirkku; Isaksson, Nea; Nyman, Mikko; Nyman, Anna; Peltola, Ville; Lähdesmäki, Tuire (Frontiers in Pediatrics, 2021)
Background Children with encephalitis have increased risk for long-term neurological sequelae. We investigated minor neurological dysfunction (MND) and cognitive performance as a measurement for long-term outcome of encephalitis in childhood. Materials and Methods Children with encephalitis (n=98) treated in Turku University Hospital during the years 1995-2016 were retrospectively identified. We included the patients without severe developmental delay before the encephalitis and without recorded neurological disability caused by encephalitis. MND was assessed using the Touwen examination. Age-appropriate Wechsler Intelligence Scale was used to determine the full-scale intelligence quotient (IQ). Residual symptoms in everyday life were evaluated using a questionnaire. Results Forty-two subjects participated in the study and returned the questionnaire regarding residual symptoms. The median age was 4.3 years at the time of encephalitis, and 11.3 years at the time of the Touwen examination (n=41) and the cognitive assessment (n=38). The Touwen examination indicated MND in 29 of 41 participants (71%; simple MND in 16 and complex MND in 13 patients). The median full-scale IQ was lower in participants with MND compared with participants without MND (98 vs 110, p=0.02). Participants with IQ<85 (n=5) had lower median age at acute encephalitis compared to participants with IQ ≥85 (n=33) (1.8 vs. 5.3 years, p=0.03). Problems in daily performance were reported in participant with MND (p=0.2) and low full-scale IQ (p=0.008). Conclusions The prevalence of MND was high and it was related to lower cognitive performance after childhood encephalitis. Younger age at acute encephalitis was a risk factor for lower cognitive performance.